Role of Ethnocentrism, Animosity, and Foreign Product Judgement on Local Brand Purchase Intention - Adelia Shabrina Prameka; Putu Adi Putra Arimbawa (Ekonomi Bisnis, 2025)
The competition of local and foreign products is constantly competing for a place in the hearts of consumers. The intensity of competition between local and foreign products puts high pressure on local producers in developing countries such as Indonesia, especially to be able to compete and have their own markets. This study explores the perception of competition between local and foreign products from the consumer side, with a special focus on the relationship between consumer ethnocentrism and animosity and foreign product judgement in influencing the intention to buy local products both directly and mediately. The questionnaire was distributed to 144 consumers of local products. The data analysis method in this study uses PLS-SEM. The results of this study succeeded in confirming the relationship between consumer ethnocentrism and animosity in local fashion products, but on the one hand, consumers did not see animosity or foreign product judgement on foreign products as factors that influenced purchasing decisions on local products. However, consumer preferences for purchasing domestic products are not influenced by the perception of foreign products. On the other hand, the decision to buy local products is also driven by consumer preferences for domestic products (consumer ethnocentrism) rather than feelings of hatred for a nation (animosity) or judgment of foreign products. This research makes a valuable contribution in understanding consumer behavior towards local products